2022
DOI: 10.3390/nu14112349
|View full text |Cite
|
Sign up to set email alerts
|

Glucose as a Potential Key to Fuel Inflammation in Rheumatoid Arthritis

Abstract: Glucose is the most important source of energy and homeostasis. Recent investigations are clarifying that glucose metabolism might be altered in rheumatoid arthritis (RA), which would play a role in the inflammatory phenotype of rheumatoid synovial fibroblasts. It may also play a role in a variety of autoimmune diseases’ pathophysiology by modulating immune responses and modifying autoantigen expressions. The research into glucose and its metabolism could lead to a better understanding of how carbohydrates con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…45 Second, the persistence of hyperglycemia may promote the formation of advanced glycation end products, which have antigenicity and induce autoimmune reactions. 46 To our knowledge, this study is the first prospective cohort study to explore the direct influence of MetS on the incident RA. Our study found that participants with MetS had a higher risk of developing RA than non-MetS participants, and the risk of RA increased with increasing MetS components.…”
Section: Discussionmentioning
confidence: 94%
“…45 Second, the persistence of hyperglycemia may promote the formation of advanced glycation end products, which have antigenicity and induce autoimmune reactions. 46 To our knowledge, this study is the first prospective cohort study to explore the direct influence of MetS on the incident RA. Our study found that participants with MetS had a higher risk of developing RA than non-MetS participants, and the risk of RA increased with increasing MetS components.…”
Section: Discussionmentioning
confidence: 94%
“…Uric acid crystals activated NLRP3 via the AMPK-mTOR-ROS-TXNIP and TLR/NF-jB pathway [86,132,133], while cholesterol crystals depended on both NF-jB and Nrf2 to activate NLRP3 [134,135]. Glycometabolism-derived DAMPs, such as glucose and its precursor-AGEsare involved in the progression of T1D, RA, and SLE by driving pro-inflammatory cytokines (e.g., TNF-a, IL-6, and IL-1b) [136][137][138][139][140] and perpetuating chronic inflammation via PI3K/Akt pathway and NF-kB signaling [141][142][143]. They may also drive disease progression by affecting epigenetic modifications and causing oxidative stress [144,145].…”
Section: Metabolite-derived Damps and Autoimmune Diseasesmentioning
confidence: 99%
“…[79,82,83,84,85,86,136,137,138,139,140,141,142,143,144,145,162,163,164,165,166,167,168,169,170,171,172,173,174] T1D, RA, SLE [80,81,95,96,97,98,99,100,101,136,137, 138,139,140,141,142,143,144,145,149,150] [106,107,108,109,110,111,112,113,159,160,161] Uric acid crystalNLRP3, TRPV4 Gout, T1D, RA[105,114,115,116,117,118,119,120,121,132,133] …”
mentioning
confidence: 99%
“…Diabetes mellitus (DM) is a metabolic disorder characterized by abnormal glucose metabolism, with glycated hemoglobin (HbA1c) serving as a crucial marker for long-term glucose control in individuals with diabetes [6]. Emerging evidence suggests a close link between DM and RA, as both conditions share common pathophysiological features, such as chronic in ammation and metabolic dysregulation [7][8][9][10]. Numerous studies have reported a relationship between RA and DM incidence; however, the risk of RA in patients with established DM has been less investigated and yielded con icting results.…”
Section: Introductionmentioning
confidence: 99%